Features of the legal regulation of social relations in Ukraine during the war - Demianchuk, Yurii; Novak, Yaroslav; Sydorenko, Vitalii; Dobrenka, Nataliіa (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The research topic «Peculiarities of legal regulation of social relations in Ukraine during the war» is relevant and important in the context of modern global conflicts and internal political tension in Ukraine. In connection with the increase in hostilities and armed conflicts in the country, there is a need to study the peculiarities of the legal regulation of these processes and their impact on social relations. This paper analyzes the legal norms and mechanisms that regulate social relations in Ukraine during the war. Special attention will be paid to martial law and wartime, legislation on military actions, protection of the rights and freedoms of citizens, as well as humanitarian problems arising as a result of the conflict.This paper analyzes the legal norms and mechanisms that regulate social relations in Ukraine during the war. Special attention will be paid to martial law and wartime, legislation on military actions, protection of the rights and freedoms of citizens, as well as humanitarian problems arising as a result of the conflict.The study will prove the importance of legal regulation of social relations in wartime to ensure the rights and interests of citizens, maintain stability and security in the country, and support humanitarian goals. The results of the research will be useful for human rights organizations, government institutions, academics and the public, who are interested in modern problems of law in the conditions of military conflict.During martial law or wartime, some rights of citizens may be limited in the interests of national security and general welfare. An important aspect of legal regulation is ensuring the protection of the rights and freedoms of citizens, especially in conditions of military conflict. This may include ensuring access to justice, protection against unlawful use of force and other measures.The study of these aspects will allow to better understand the essence of the problem and find ways to solve it in the conditions of war. The psychological aspects of the military conflict and the importance of psychological support for the population in conditions of stress and anxiety are analyzed.